The evaluation of intraocular pressure fluctuation in glaucoma subjects during submaximal exercise using an ocular telemetry sensor - Bozkurt, Banu; Okudan, Nilsel; Belviranli, Muaz; Oflaz, Ayse (Indian journal of ophthalmology, 2019)
Purpose: To evaluate the effect of acute submaximal exercise on intraocular pressure (IOP) fluctuations in open-angle glaucoma (OAG) subjects using an ocular telemetry sensor (OTS, Sensimed TriggerFish®). Methods: Twelve OAG subjects aged 45-65 years with no medical limitation for exercise were included in this prospective study. A submaximal exercise test was performed using a cycle ergometer for 20 min during which OTS voltages and metabolic parameters were recorded continuously. IOP voltages taken before, during, and after exercise were compared using the Friedman test and correlations with the metabolic parameters were evaluated using the Spearman analysis. Results: In two subjects, the OTS stopped functioning after a few hours. Median OTS measurements were 37.60 mVeq 10 min before exercise [interquartile range (IQR) 137.27], 51.75 (IQR 121.2), 62.35 (IQR 123.72), 54.6 (IQR 141.3), and 59.7 mVeq (IQR 196.7) during exercise (4 time points, 5 min apart), and 50.7 (IQR 147.35) and 64.2 mVeq (IQR 103.25) 10 and 30 min after exercise and the change was statistically non-significant (P = 0.66). No correlations were found between OTS and metabolic parameters measured at the same time points (P > 0.05). Nocturnal acrophase pattern was detected in five subjects (50%), diurnal acrophase in two patients, and double-hump in two patients. Median IOP voltages in the morning, afternoon/evening, and night were 335.84, 149.15, and 341.38 mVeq, respectively (P < 0.001). Conclusion: Continuous IOP monitoring did not reveal a remarkable voltage change in OAG patients during or immediately after exercise, but nocturnal IOP peaks in half of the patients.